Multi-target regulation of intestinal microbiota by berberine to improve type 2 diabetes mellitus - He, Qiongyao; Dong, Hui; Guo, Yujin; Gong, Minmin; Xia, Qingsong; Lu, Fuer; Wang, Dingkun (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus (T2DM) and its complications are major public health problems that seriously affect the quality of human life. The modification of intestinal microbiota has been widely recognized for the management of diabetes. The relationship between T2DM, intestinal microbiota and active ingredient berberine (BBR) on intestinal microbiota were reviewed in this paper. First of all, the richness and functional changes of intestinal microbiota disrupt the intestinal environment through the destruction of intestinal barrier and fermentation / degradation of pathogenic / protective metabolites, targeting liver, pancreas, visceral adipose tissue (VAT), etc., to affect intestinal health, blood glucose and lipids, insulin resistance and inflammation. Then, we focus on BBR, which protects the composition of intestinal microbiota, the changes of intestinal metabolites and immune regulation disorder of the intestinal environment as the therapeutic mechanism as well as its current clinical trials. Further research can analyze the mechanism network of BBR to exert its therapeutic effect according to its multi-target compound action, so as to provide a theoretical basis for the use of different phytochemical components alone or in combination to prevent and treat T2DM or other metabolic diseases by regulating intestinal microbiota.